Fire risk management : principles and strategies for buildings and industrial assets - Fiorentini, Luca, 1976-; Dattilo, Fabio (John Wiley & Sons, Inc., 2023)
"Heraclitus, an ancient Greek philosopher, asserted that everything in the world flows ("Panta Rei") and that fire represents universal becoming better than anything else because fire itself is the "archeÌ¹", the principle from which all things are generated. For the philosopher, this becoming is not random and chaotic but is regular and orderly, provided one knows the rules. In this volume, we have tried to explain the complex rules governing fire in a simple way, using methods, from the simplest to the most refined, such as the engineering approach. Studying the development of smoke and heat in fires, knowing the effects they have on people and buildings, helps a great deal in adopting the right strategies for preventing and containing fires. But the approach taken in the book is deliberately holistic, in the sense that each individual strategy can have a great influence on the others, and therefore fire prevention must be seen as a whole. And as a whole, the success (or failure) of the strategies implemented also depends on the behaviour of the people involved, behaviour that must be framed within a safety management perspective. A volume that purports to present the historical discipline of fire prevention but with a new methodological approach based on the performance to be achieved rather than on strongly prescriptive but often uncritical methods and requirements"--